Navigating the challenges of medical English education: a novel approach using computational linguistics - Gayle,Alberto A (PeerJ PrePrints, 2016)
Recent studies have shown that International medical graduates (IMG) comprise a substantial and increasingly larger share of the medical workforce, internationally. IMGs wishing to work in English-speaking countries face many challenges. And overcoming such challenges plays an important role in ensuring a more comfortable transition and improved outcomes for patients. This study addresses one such area of concern: the efficient acquisition of advanced language competence for use in the medical workplace. This research also addresses the needs of medical students and practitioners in other countries, where English is not the primary language. Medical terminology and phrasing is based on a tradition spanning more than 2500 years—a tradition that cuts across typical linguistic and cultural boundaries. Indeed, as is commonly understood, the language required by doctors and other medical professionals varies substantially from the norm. In the present study, this dynamic is exploited to identify and characterize the language and patterns of usage specific to medical English, as it is used in practice and reporting. Overall, constructions comprised of preposition-dependent nouns, verbs and adjectives were found to be most prevalent (38%), followed by prepositional phrases (33%). The former includes constructions such as “present with”, “present to”, and “present in”; while constructions such as “of … patient”, “in … group”, and “with … disease” comprise the latter. Preposition-independent noun and verb-based constructions were far less prevalent overall (18% and 5%, respectively). Up to now, medical language reference and learning material has focused on relatively uncommon, but essential, Greek and Latin terminology. This research challenges this convention, by demonstrating that medical language fluency would be acquired more efficiently by focusing on prepositional phrases or preposition-dependent verbs, nouns, and adjectives in context. This work should be of high interest to anyone interested in improved communication competence within the English-speaking medical workplace and beyond. What is already known on this subject : * International medical graduates make up a substantial portion of the medical workforce * Imperfect medical English creates challenges for international medical graduates * Subideal language impacts credibility and has been associated with increased risk to patients What this paper adds : * Preposition-dependent terms, following Germanic usage patterns, dominate medical English * Complex terms derived from Greek and Latin are far less prevalent than assumed * Medical English learning expected to be expedited by focus on preposition-dependent terms
Keywords: computational linguistics; medical English; medical communications; medical humanities; international medical graduations; english for specific purposes; social medicine; text mining; interpersonal communication